PATRIARCHY AND WOMEN’S SUBORDINATION: STUDY OF NYAI ONTOSOROH IN PRAMOEDYA ANANTA TOER’S THIS EARTH OF MANKIND” - mei handayani (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
This study analyzes patriarchy and women's subordination in the Novel “This Earth of Mankind” written by Pramoedya Ananta Toer. Colonialism brought patriarchal status and women's subordination to indigenous women, while patriarchy gave women the lowest authority and authority. Nyai Ontosoroh is a native Javanese woman; her husband is Dutch, who lived and was part of the Dutch colonialism. She was a mistress who sold to Dutch shows. This study aimed to explore the patriarchal status and subordination of women during the Dutch colonial era described by Nyai Ontosoroh in Pramoedya Ananta Toer's novel “This Earth of Mankind” and to reveal the patriarchal and female factors that occur in the protagonist in this novel. The data source is the historical novel by Pramodedya Ananta Toer entitled